The Long-Term Safety and Efficacy of Opioids: A Survey of 84 Selected Patients with Intractable Chronic Noncancer Pain - C Peter N Watson; Judy Watt-Watson; Mary Chipman (Pain Research and Management)
BACKGROUND: The use of opioids for chronic noncancer pain (CNCP) remains controversial. Despite a number of randomized controlled trials showing efficacy and safety in the short term, long-term data are limited.